THE RELATIONSHIP OF NURSE KNOWLEDGE ABOUT THERAPEUTIC COMMUNICATION WITH IMPLEMENTATION OF THERAPEUTIC COMMUNICATION IN CHILDREN AGE OF PRASEKOLAH (6 YEARS) IN THE CARE ROOM 1 POLEWALI MANDAR RSUD - Firmansyah, Andan (Bina Generasi : Jurnal Kesehatan, 2017)
Background: Therapeutic communication is a way to foster therapeutic relationships between nurse-clients. In the communication process occurs the delivery of information, which can be used as an effective tool in providing nursing care to children. There are several possibilities of less successful therapeutic communication in children such as influenced by lack of knowledge of therapeutic communication, nurse attitude, education level, experience, environment, number of perceived power less and others. Treatment room 1 is a children's disease room with a bed capacity of 10 pieces with the number of preschool children as many as 18 people. According to Minister of Health Decree No. 262 year 2000 Ratio of number of beds with number of nurses in non-educational C type RS, 2 beds versus 3-4 nurses. Looking at the data on the number of nurses and the number of bed capacity in the treatment room 1 RSDU Polewali Mandar is very unbalanced, so the likelihood of successful therapeutic communication in children is reduced and can affect the knowledge and attitude of nurses in therapeutic communication in preschoolers. To overcome the problem one of them is by using effective therapeutic communication that will and is being done nursing actions such as digging perassaan, mind, behavioral changes so that will be able to solve psychological problems in preschool age children.The purpose of this study is to know the relationship nurse knowledge level about communication therapeutic with the implementation of therapeutic communication in 6-year-old preschool children in the treatment room 1 RSUD Polewali Mandar. with type of research using cross sectional study The population of this research is mother of balita which is in sub district of Matakali district Polewali Mandar with number 2389 mother of toddler. Sampling is done by total sampling method that is all nurses who work in treatment room I as much as 21 implementing nurses.wwwwwwThe results showed that there was a correlation between the level of nurse knowledge about therapeutic communication with the implementation of therapeutic communication in preschool age children (6 years) in the treatment room 1 RSUD Polewali Mandar. Means there is a tendency that the higher knowledge the better the implementation of therapeutic communication itself, especially in children with significant degree of significance p = 0.007> 0.05 means H1 is rejected and H0 received. Expected to the Public Hospital dareah Polewali Mandar In order to get the maximum service improvement, so that patients and visitors feel satisfied with the services provided.